Investigations into the cutting and wear characteristics of TiCN-CrN coated C 80 steels - Cakan, Ahmet; Ozkaner, Vedat; Yildirim, M. Mustafa (Carl Hanser Verlag, 2008)
Hard coatings of titanium carbonitrides (TiCN) and chromium nitrides (CrN) are now commonly used to protect the surfaces of cutting tools from the effects of wear and corrosion. In the work presented here the surfaces of the cutting edges of tools made of unalloyed C80 steel are coated with a thin layers of TiCN and CrN coatings using the Cathodic Arc-Vapour (CAVD) deposition technique. The cutting characteristics and wear behaviour of the cutting tools so treated were then investigated experimentally on a conventional lathe. The change in the chemical composition and properties of the nitride coated surfaces is investigated using both SEM photography with line scan analysis and by X-ray diffraction (XRD). Cutting tests and wear behaviour of tools, the cutting edges of which were coated with very thin TiCN and CrN coatings, were investigated directly using an on-line monitoring system. Amongst other things the results revealed the TiCN coated cutting tools to be more wear resistant than those coated with CrN coatings.
Experimentelle Untersuchungen über Schneid- Und Verschleiß charakteristiken der TiCN-CrN-Beschichteten C 80-Stähle